Chimeric L2-Based Virus-Like Particle (VLP) Vaccines Targeting Cutaneous Human Papillomaviruses (HPV) - Huber, Bettina (PLoS One, 2017)
Common cutaneous human papillomavirus (HPV) types induce skin warts, whereas species beta HPV are implicated, together with UV-radiation, in the development of non-melanoma skin cancer (NMSC) in immunosuppressed patients. Licensed HPV vaccines contain virus-like particles (VLP) self-assembled from L1 major capsid proteins that provide type-restricted protection against mucosal HPV infections causing cervical and other ano-genital and oro-pharyngeal carcinomas and warts (condylomas), but do not target heterologous HPV. Experimental papillomavirus vaccines have been designed based on L2 minor capsid proteins that contain type-common neutralization epitopes, to broaden protection to heterologous mucosal and cutaneous HPV types. Repetitive display of the HPV16 L2 cross-neutralization epitope RG1 (amino acids (aa) 17–36) on the surface of HPV16 L1 VLP has greatly enhanced immunogenicity of the L2 peptide. To more directly target cutaneous HPV, L1 fusion proteins were designed that incorporate the RG1 homolog of beta HPV17, the beta HPV5 L2 peptide aa53-72, or the common cutaneous HPV4 RG1 homolog, inserted into DE surface loops of HPV1, 5, 16 or 18 L1 VLP scaffolds. Baculovirus expressed chimeric proteins self-assembled into VLP and VLP-raised NZW rabbit immune sera were evaluated by ELISA and L1- and L2-based pseudovirion (PsV) neutralizing assays, including 12 novel beta PsV types. Chimeric VLP displaying the HPV17 RG1 epitope, but not the HPV5L2 aa53-72 epitope, induced cross-neutralizing humoral immune responses to beta HPV. In vivo cross-protection was evaluated by passive serum transfer in a murine PsV challenge model. Immune sera to HPV16L1-17RG1 VLP (cross-) protected against beta HPV5/20/24/38/96/16 (but not type 76), while antisera to HPV5L1-17RG1 VLP cross-protected against HPV20/24/96 only, and sera to HPV1L1-4RG1 VLP cross-protected against HPV4 challenge. In conclusion, RG1-based VLP are promising next generation vaccine candidates to target cutaneous HPV infections.